Molecular Action of Hydroxytyrosol in Attenuation of Intimal Hyperplasia: A Scoping Review - Vijakumaran, Ubashini; Yazid, Muhammad Dain; Hj Idrus, Ruszymah Bt; Abdul Rahman, Mohd Ramzisham; Sulaiman, Nadiah (Frontiers in Pharmacology, 2021)
Objective: Hydroxytyrosol (HT), a polyphenol of olive plant is well known for its antioxidant, anti-inflammatory and anti-atherogenic properties. The aim of this systematic search is to highlight the scientific evidence evaluating molecular efficiency of HT in halting the progression of intimal hyperplasia (IH), which is a clinical condition arises from endothelial inflammation. Methods: A systematic search was performed through PubMed, Web of Science and Science Direct based on pre-set keywords which are Hydroxytyrosol OR 3,4-dihydroxyphenylethanol, AND Intimal hyperplasia OR Neointimal hyperplasia OR Endothelial OR Smooth muscles. Eighteen in vitro and three in vitro and in vivo studies were selected based on a pre-set inclusion and exclusion criteria. Results: Based on evidence gathered, HT was found to upregulate PI3K/AKT/mTOR pathways and supresses inflammatory cytokines such as IL-1β, IL-6, E-selectin, P-selectin, VCAM-1, and ICAM-1 in endothelial vascularisation and functioning. Two studies revealed HT disrupted vascular smooth muscle cells (SMC) cell cycle by dephosphorylating ERK1/2 and AKT pathways. Therefore, HT was proven to promote endothelisation and inhibit vascular SMCs migration thus hampering IH development. However, none of these studies described the effect of HT collectively in both vascular endothelial cells (EC) and SMCs in IH ex vivo model. Conclusion: Evidence from this concise review provides an insight on HT regulation of molecular pathways in reendothelisation and inhibition of VSMCs migration. Henceforth, we propose effect of HT on IH prevention could be further elucidated through in vivo and ex vivo model.